Chemical composition change of oat plants and the accumulation of NPK in the yield when applying a mineral fertilizer modified with a biological product - G. V. Ermolaeva (Зерновое хозяйство России, 2023)
The purpose of the current study was to determine changes in the chemical composition of oat plants and the accumulation of the main nutrients when applying mineral and biomodified fertilizers. The study of oats sown after spring barley was carried out on leached heavy loamy chernozem in 2016–2018. The objects of the study were the mineral fertilizer ‘Azofoska’, the biological product ‘BisolbiFit’ (powder form based on live beneficial bacteria Bacillus subtilis Ch-13), the spring oats variety ‘Rysak’. The weather and climatic conditions during the years of study were quite diverse, which made it possible to objectively estimate the study results. There has been found that the oat productivity over the years of study (2016–2018) was at the level of 2.15–2.30 t/ha. The use of the studied fertilizers in the trial, such as ‘Azofoska’ and ‘BisolbiFit’, contributed to oat productivity increase by 2.3–7.0 % compared to the variant without fertilization (control). The maximum productivity increase was obtained in the variant with modified ‘Azofoska’ (AZKm) at a dose of 15 kg/ha a.i., grain yield in this variant was 2.30 t/ha, exceeding the control by 0.15 t/ha. The difference between the variants of the trial was not significant (0.05–0.15 t/ha) with HSR05 = 0.17 t/ha. The coefficient of consumption of nitrogen, phosphorus, and potassium by oat plants on average was 63, 39 and 65 %. The use of a microbiological product based on live beneficial bacteria Bacillus subtilis Ch-13 (for the biomodification of ‘Azofoska’) contributed to the maximum increase in the payback of 1 kg of NPK by the yield increase. The highest payback from 1 kg a.i. fertilizers was established when applying ‘Azofoska’ modified with the biological product ‘BisolbiFit’ at a dose of 7.5 kg/ha a.i. (½ AZKm) and amounted to 5.8 kg/kg.